INTERPERSONAL COMMUNICATION OF THE HEALING CYCLING CLUB COMMUNITY IN BUILDING SOLIDARITY - Kartika, Risma; Luhur , Purwoadji Pambudhi (Universitas prof. Dr. Moestopo (Beragama), 2025)
This study analyzes the role of interpersonal communication in building community solidarity within the Healing Cycling Club (HCC). Founded in 2020, this cycling community integrates cycling activities with the concept of healing, emphasizing togetherness, solidarity, and social support. The findings indicate that five qualities of interpersonal communication according to DeVito. Openness, empathy, supportive attitude, positive attitude, and equality are actively practiced in the daily interactions of HCC members. Openness is manifested through sharing information and personal experiences, building trust. Empathy is shown through genuine care and mutual support, both during cycling activities and in facing personal challenges. Supportive and positive attitudes are reflected in encouragement, appreciation, and constructive problem-solving, maintaining a harmonious atmosphere. Equality ensures that every member feels valued and has equal opportunities to participate. Solidarity within HCC is strongly realized through collective practices, where members share awareness and responsibility for the community’s success and sustainability. This is supported by the synergy of shared interest in cycling and the geographic location in Bogor, which facilitates regular interaction.